The Creative ImprovisationRicoeur, Florensky and Balthasar: Between Reference Systems and Creative Freedom (Itinera, 2015)
The aim of this paper is to reflect on improvisation by means of discussing the relation between system and freedom. I begin with a reflection on the meanings of improvisation. Than, following Ricoeur’s philosophy and Florenskij’s iconology I show that creativity works like an innovation within the tradition. At the end, I claim that Balthasar’s theological aesthetics gives interesting contributions to the hermeneutic of testimony, that, in turn, helps to understand why the connection between system and freedom is key to the process of improvisation.